Promise and paradox: A critical sociohydrological perspective on small-scale managed aquifer recharge - Basel, Britt; Hoogesteger, Jaime; Hellegers, Petra (Frontiers in Water, 2022)
Small-scale managed aquifer recharge (MAR) has significant potential as a bottom-up, community-based adaptation solution for increasing local groundwater availability and reducing the experience of drought for small-holder agriculturalists and rural populations. Using a suite of low-tech and low-cost techniques, small-scale MAR increases the infiltration of surface water runoff to replenish groundwater and deliver a suite of societal and ecosystem benefits. While the technique is hydrologically promising, populations may not act, implementation may not be permitted, interventions may not be effective for the population in question, or unexpected consequences (paradoxes) may result. For small-scale MAR to effectively reduce the experience of drought, it is imperative to unravel how such interventions playout within the complexity of the sociohydrological system in which they are implemented. Building on previous conceptualizations of the sociohydrological system, we apply the lens of political ecology to conceptualize the interplay between biophysical, climate, and social systems, and explore considerations, feedbacks, and potential paradoxes in the uptake, implementation, and effectiveness of small-scale MAR interventions. We show that within the parameters of climate trends, small-scale MAR may serve to increase the functionality of ecosystems and reduce the impact of climate extremes, while protecting livelihoods and supporting society. In a positive feedback loop, small-scale MAR may both reduce the likelihood of experiencing drought while simultaneously increasing the ability and likelihood of the population to cope with or further avoid drought. Paradoxes and negative feedbacks, however, must be avoided. Specific factors, and how such factors interplay, will be different in each context where small-scale MAR is implemented. Conceptualizing the sociohydrological system in which small-scale MAR is implemented, including explicitly accounting for climate trends and using a power-sensitive approach, allows us to avoid overestimating or over simplifying small-scale MAR as a solution, while supporting practical and effective implementation.